2018
DOI: 10.5603/gp.a2018.0091
|View full text |Cite
|
Sign up to set email alerts
|

Common Methylenetetrahydrofolate Reductase Polymorphisms (A1298C & C677T) in Ectopic Trophoblasts and Methotrexate Treatment Failure in Tubal Pregnancies

Abstract: Objectives: The success rate of methotrexate (MTX) therapy varies among tubal ectopic pregnancies. Common methylenetetrahydrofolate reductase (MTHFR) polymorphisms (C677T&A1298C) have been suggested to alter MTX effect. This study aimed to assess and compare MTX treatment failure rates with respect to MTHFR polymorphisms in trophoblasts of ectopic tubal pregnancies. Material and methods: A retrospective chart review of tubal ectopic pregnancies was conducted and 34 eligible cases were found. Paraffinized block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Chen Y et al concluded that C677T polymorphism of MTHFR predicts nonresponse and adverse effects of MTX in juvenile idiopathic arthritis . However, two studies implied that MTHFR C677T was not associated with MXT failure and β ‐hCG concentration changes during MTX treatment in patients with tubal EP . Interestingly, our results showed that CC carriers had a lower success rate than CT and TT carriers by first MTX injection and another dosage of MTX treatment.…”
Section: Discussionmentioning
confidence: 49%
“…Chen Y et al concluded that C677T polymorphism of MTHFR predicts nonresponse and adverse effects of MTX in juvenile idiopathic arthritis . However, two studies implied that MTHFR C677T was not associated with MXT failure and β ‐hCG concentration changes during MTX treatment in patients with tubal EP . Interestingly, our results showed that CC carriers had a lower success rate than CT and TT carriers by first MTX injection and another dosage of MTX treatment.…”
Section: Discussionmentioning
confidence: 49%